Mastery of Arabic Speaking Skills among Students: A Study on the Influence of the Linguistic Environment - Reza Fachrial Suhardi; J. Sutarjo (Universitas Islam Negeri Jurai Siwo Lampung, 2024)
This study aims to determine the relationship between the language environment and the Arabic speaking skills of the eighth-grade students at the Modern Islamic Boarding School Insan Mulia Batanghari for for the 2022/2023 academic year. This research design uses a quantitative approach with correlation research methods. The data collection instruments in this study are tests, questionnaires, and documentation. The data analysis technique used in this study is the Pearson correlation analysis technique with the moment product formula. This study found that the language environment plays a vital role in acquiring, training, and mastering Arabic speaking skills. That is based on research results that show a positive, significant, and strong correlation between the language environment and the Arabic speaking skills of the eighth-grade students at the Modern Islamic Boarding School Insan Mulia Batanghari for the 2022/2023 academic year.